Studi Analisis terhadap Eksistensi Mata Kuliah Hadits Tarbawi - Munir Abbas Bukhori (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2011)
The title of this article is the study of Existence Analysis Subjects Tarbawi Hadith. From this article it can be concluded that the Hadith tarbawi is one of the courses for students of the Faculty of Islamic Studies Department Tarbiyah or Islamic Religious Education, as MKDK with weights two Credits and delivered in semester one. The course is presented as a briefing to the students to understand and appreciate the clues prophet Muhammad SAW and can convey to the learners after becoming a teacher. The mention of Hadith Tarbawi is an effort for the election of the hadiths that there will be MKDK each department. Because virtually all the hadith of the Prophet are as tarbiyah/education for students, as advice to be followed and Uswah (example) for a Muslim. Although the naming of hadith tarbawi including corny, but the benefit for students especially for students of Islamic Religious Education, then it can be accepted. Source books of this subject, many in the access of al-Lu'lu 'wa al-Marjan and Riyadh al-Shalihin. Imam Nawawi much influence on this subject. We recommend library books complement source, as a service to students in addition to devotion to the Islamic sciences